Solusi Praktis untuk Ibu-Ibu Pengungsi IOM Surabaya: Perancangan dan Pembuatan Alat Pemipih Adonan Skala Rumah Tangga - Muhammad Yanuar Herdiansyah; Rani Nur Aini; Daniella Particulariseta Kindangen; Miftakhul Huda; Reyna Angelia Nauval (ABDIMAS TERAPAN : Jurnal Pengabdian Kepada Masyarakat Terapan, 2025)
This community service program, conducted by students of Universitas 17 Agustus 1945 Surabaya at the IOM Surabaya refugee settlement, aimed to provide a practical solution for refugee housewives in the field of culinary skills, specifically in dough preparation. The project focused on the design and implementation of a household-scale dough flattening tool, complemented by training sessions on its usage and food product processing. Through educational and participatory approaches, the program successfully fostered entrepreneurial interest and technical skills among the participants. With the introduction of an innovative, hinge-spring-based flattening device, the women were able to understand and efficiently apply proper dough-handling techniques. This initiative opened opportunities for small-scale businesses that could support the economic independence of refugee families.